Partially Coherent, Radially Polarized Beam with Annular Apodization - C. Mariyal; P. Suresh; K. B. Rajesh; T. V. S. Pillai (The Scientific World Journal)
Based on the vectorial Debye theory, the tight focusing properties of partially coherent, radially polarized vortex beams are investigated in detail. In this paper, we propose to use an amplitude modulated filter in combination with a high NA lens to generate long focal depth in the focal region. Numerical results show that the generation of long focal depth of FWHM (22.08λ) is achieved, which finds useful application in microscopy techniques such as particle acceleration, laser processing, optical micromanipulation, and beam shaping.